Wi-Fi Received Signal Strength-based Indoor Localization System Using K-Nearest Neighbors fingerprint integrated D* algorithm - Tanatthep Jarawan; Patcharin Kamsing; Peerapong Tortceka; Shariff Manuthasna; Warunyu Hematulin; Tachodom Chooraks; Thaweerath Phisannupawong; Sitthirak Sanzkarak; Sookaseam Munakhud; Thananorn Somjit (My University, 2021)
The indoor localization system is essential since the Global Positioning System cannot give an accurate position indoors, especially when several floor plans are considered. Wi-Fi received signal strength becomes an alternative indicator for indoor localization systems. The experiment proposed a localization system created by integrating and working between the K-Nearest Neighbors algorithm and the D*algorithm. The result illustrates the optimal path from the start point to the target point by avoiding the obstacle performing exceptionally well. The K-Nearest Neighbors algorithm provide the result for localization with Root Mean Square Errors of displacement at 1.190 meters, 2.491 meters, and 1.363 meters of X-Axis Y-Axis, respectively. The proposed indoor localization system can have various applications considering different environmental factors in different applications, such as the size of unmanned aerial vehicles when applying indoor unmanned aerial vehicles.
Keywords: Indoor and Outdoor Localization Technologies; Robotics and Sensor-Based Localization; Underwater Vehicles and Communication Systems